Mothers going the distance: A brief review of postpartum return to elite endurance sport - Hewitt, C. M.; Campbell, M. K.; Thornton, J. S. (Exercise and Sport Sciences Reviews, 2026)
The purpose of this review was to summarize existing information and identify critical research gaps around pregnancy and the postpartum period in elite endurance athletes. Current literature is primarily exploratory and lacks high-level evidence. We anticipate that continued research will help in identifying the best support mechanisms to offset setbacks associated with pregnancy and postpartum recovery in elite female athletes.